Review of follow-up of clinical success of implant-supported complete dental prostheses - GRECO,Gustavo Diniz (2014)
OBJECTIVE: The aim of this study was to assess the clinical success rate of implant-supported complete dental prostheses, which are being used as a feasible alternative in planning of oral rehabilitation. Over the years, the two-stage surgical protocol has increasingly been replaced by immediate loading procedures, especially in the mandibular anterior region in cases of rehabilitation of completely edentulous patients. This procedure has become feasible due to the high success rate of the technique with very satisfactory results. METHODS: By means of a literature review focused on published articles with clinical follow-up between 8 and 15 years. RESULTS: Implants placed in the mandible had higher success rates than those inserted in the maxilla. Cases with longer follow-up periods, 15 years, showed higher success rates in comparison with follow-up periods of 8 and 10 years. CONCLUSION: Success rates of implant-supported complete dental prostheses are very high.